EFFECT OF PROFITABILITY AND LIQUIDITY ON STOCK RETURNS ON INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2015-2018 - Gwyneth Heiddy Limbong; Harman Malau (Jurnal Ekonomis, 2020)
This study aims to determine the effect of profitability and liquidity on stock returns. The dependent variable is the return on equity (ROE) and current ratio (CR) and uses stock returns as an independent variable. The data collection method used is using purposive sampling, the source of which is secondary data, and obtained from the company's annual or financial statements. This study uses samples from infrastructure sector companies in the energy, toll roads, ports, airports & the like and telecommunications sub-sector that were listed on the Indonesia Stock Exchange in 2015-2018. The analytical method used is the multiple regression method. The results showed that profitability did not affect stock returns and liquidity does not affect stock returns. And the simultaneous effect of return on equity (ROE) and current ratio (CR) on stock returns does not affect infrastructure sector companies listed on the Indonesia Stock Exchange in 2015-2018.